Kualitas Pelayanan Program Bus Sekolah Trans Gianyar Bagi Pelajar di Kabupaten Gianyar (Studi Kasus Trayek TH-01 Batubulan – Sukawati) - Surya Dewi, Ni Putu Indah; Sastra Wijaya, Komang Adi; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2018)
ABSTRACT One form of public service needed by the public is public transport services. But this time, in Gianyar regency public transportation tends to be abandoned by the public due to the low level of service provided by the government. It also affecting the students to use motorcycles when they go to school instead of using public transport. Responding to the phenomenon, the Department of Transportation Gianyar Distric providing free school bus services called Trans Gianyar. This research was conducted using qualitative descriptive method. The indicators that used in this research are (1) tangibles, (2) reliability, (3) responsiveness, (4) assurance, (5) emphaty. The result of this study indicate Trans Gianyar is still not running optimally yet. It can be seen from the five indicators that only emphaty expected the target, while the others are still not running optimally. The obstacles in this reseach are lack of human resource and founding sources. Keywords: Quality, Services, Gianyar